O ensino primário no Colégio Farroupilha : do processo de nacionalização do ensino à LDB nº 4.024/61 (Porto Alegre/RS: 1937/1961) - Jacques, Alice Rigoni (2015)
The present research, which is inserted in the field History of Education discusses the primary school of Colégio Farroupilha, which is located in Porto Alegre/RS, in the period that goes from the nationalization of education until the implementation of the law, emitted in 1961, called: ―Lei de Diretrizes e Bases da Educação Nacional‖. This study covers the years of 1937-1961, a coping period that the school organizations had to face due to the strong campaign of nationalization in German schools and societies. In these scenarios, the structure and the administrative-pedagogical organization of the school had to adjust to transformations in the political context of the country. From the norms determined by the state and by the federal government, there were several curricular changes such as: prohibiting the use of the German language in class, not allowing the conversation in German between students in the schoolyard and between teachers and students, prohibiting the circulation of foreign books inside the institution, the government regulation of holidays and vacation, teaching methods and the way teachers led the pedagogical relationship and disciplinary practices. This research sought to discuss how the school, being private and having German origins, has adjusted to the new government proposals and changes in the administration. This research aims to investigate the changes in the school from the current legislation, for example in the faculty and students of schools, in the festivals and celebrations and in educational practices developed in this period. It also aims to understand how the school, teachers, directors and other agents used these norms and guidelines of this code of National Education, - which the state took over, by establishing their fundamental principles and monitoring its application, - to constitute their teaching practice and match the political and educational expectations established in the analyzed period. Through the theoretical support and the analyzed documents (the annual reports from the direction of primary education which were presented in the school Maintainer Meetings, the school notebooks, the school newspapers, the Teaching Magazines of Rio Grande do Sul, the photographs of events, the inspection records, the official correspondences and the interviews), the research was established. The final considerations focus on the issue that the campaign of nationalization in education sought to socially regulate the national feeling, causing the school to assume the characteristics of the systematic and repressive action of local authorities. Moreover, Colégio Farroupilha became a target and used to be monitored during this process, because this action involved a rigid policy of nationalization in private schools. In part, the school sought to fulfill the governmental inspections and norms. We can say that the changes that have reached Colégio Farroupilha were not exclusive of that institution, but it is a story, to a certain extent, of resistance and adjustments to government measures which aimed one goal: the ideal nationalist institution.